2022
DOI: 10.3389/fcimb.2022.854505
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Mycoplasma Pneumoniae Among Children in Beijing Before and During the COVID-19 Pandemic

Abstract: ObjectiveMycoplasma pneumoniae (M. pneumoniae) is an important pathogen of community acquired pneumonia. With the outbreak of coronavirus disease 2019 (COVID-19), the prevalence of some infectious respiratory diseases has varied. Epidemiological features of M. pneumoniae in children from Beijing (China) before and during the COVID-19 pandemic were investigated.MethodsBetween June 2016 and May 2021, a total of 569,887 children with respiratory infections from Children’s Hospital Affiliated to Capital Institute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 28 publications
4
15
0
Order By: Relevance
“…37°C is the optimum growth temperature for MP, which grows best in the hottest months in China such as July, August and September. But in 2020 fewer patients visited clinicians following the outbreak of the COVID-19 pandemic and restrictive means against COVID-19 cut down the incidence of respiratory infections, there was a considerable reduction in the positive rate of MP since March, which remained at a comparatively low level afterwards, consistent with previous ndings in other studies [29][30][31]. At the start of the new term, the "Guidelines for the Prevention and Control of the Novel Coronavirus Pneumonia in Primary and Secondary Schools" was issued by the Ministry of Education to give a guide and assistant on the prevention and control of the epidemic in schools.…”
Section: Discussionsupporting
confidence: 84%
“…37°C is the optimum growth temperature for MP, which grows best in the hottest months in China such as July, August and September. But in 2020 fewer patients visited clinicians following the outbreak of the COVID-19 pandemic and restrictive means against COVID-19 cut down the incidence of respiratory infections, there was a considerable reduction in the positive rate of MP since March, which remained at a comparatively low level afterwards, consistent with previous ndings in other studies [29][30][31]. At the start of the new term, the "Guidelines for the Prevention and Control of the Novel Coronavirus Pneumonia in Primary and Secondary Schools" was issued by the Ministry of Education to give a guide and assistant on the prevention and control of the epidemic in schools.…”
Section: Discussionsupporting
confidence: 84%
“…investigated the epidemiology of M. pneumoniae in Chinese children with respiratory infections from June 2016 to May 2021. 45 Reportedly, the positivity rates did not differ significantly in relation to the season, age group, gender, or period (before or during the COVID-19 pandemic) as revealed from the M. pneumoniae specific-IgM antibody rapid immuno-chromatographic assay of the serum specimens of 569,887 pediatric patients. 45…”
Section: Discussionmentioning
confidence: 84%
“…44 A retrospective study by Cheng et al investigated the epidemiology of M. pneumoniae in Chinese children with respiratory infections from June 2016 to May 2021. 45 Reportedly, the positivity rates did not differ significantly in relation to the season, age group, gender, or period (before or during the COVID-19 pandemic) as revealed from the M. pneumoniae specific-IgM antibody rapid immunochromatographic assay of the serum specimens of 569,887 pediatric patients. 45 Treatment strategies for CAP largely rely on the presented clinical symptoms (mild or severe) and infection type (bacterial-and/or viral-associated pneumonia; co-infection) suspected in patients with CAP.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In the summer of 2019, data revealed that a new round of outbreaks had begun. Then, as a result of the strict COVID‐19 containment policies implemented from 2020, this outbreak was effectively stopped [19], with a similar phenomenon seen in other regions of the world. A similar trend in outbreaks was observed in Japan from 1981 [20].…”
Section: Epidemic Characteristics Of M Pneumoniaementioning
confidence: 99%